The Difficulty of Believing in Writing Across the Curriculum - Anne Ellen Geller (Journal of the Assembly for Expanded Perspectives on Learning, 2009)
What would happen if we tried to consider writing-acrossthe- curriculum work through the lens of Peter Elbows methodological believing? If we were to believe that every faculty person in the university is a writer, thinks about writing, and teaches writing in his or her own way, what virtues would we find that doubting leads us to disqualify?